Documentation dynamics: Note composition, burden, and physician efficiency. (21st November 2022) - Apathy, Nate C.; Rotenstein, Lisa; Bates, David W.; Holmgren, A. Jay
Abstract: Objective: To analyze how physician clinical note length and composition relate to electronic health record (EHR)‐based measures of burden and efficiency that have been tied to burnout. Data Sources and Study Setting: Secondary EHR use metadata capturing physician‐level measures from 203, 728 US‐based ambulatory physicians using the Epic Systems EHR between September 2020 and May 2021. Study Design: In this cross‐sectional study, we analyzed physician clinical note length and note composition (e.g., content from manual or templated text). Our primary outcomes were three time‐based measures of EHR burden (time writing EHR notes, time in the EHR after‐hours, and EHR time on unscheduled days), and one measure of efficiency (percent of visits closed in the same day). We used multivariate regression to estimate the relationship between our outcomes and note length and composition. Data Extraction: Physician‐week measures of EHR usage were extracted from Epic's Signal platform used for measuring provider EHR efficiency. We calculated physician‐level averages for our measures of interest and assigned physicians to overall note length deciles and note composition deciles from six sources, including templated text, manual text, and copy/paste text. Principal Findings: Physicians in the top decile of note length demonstrated greater burden and lower efficiency than the median physician, spending 39% more time in the EHR after hours ( p  < 0.001) and closing 5.6 percentage points fewer visits on the same day ( p  < 0.001). Copy/paste demonstrated a similar dose/response relationship, with top‐decile copy/paste users closing 6.8 percentage points fewer visits on the same day ( p  < 0.001) and spending more time in the EHR after hours and on days off (both p  < 0.001). Templated text (e.g., Epic's SmartTools) demonstrated a non‐linear relationship with burden and efficiency, with very low and very high levels of use associated with increased EHR burden and decreased efficiency. Conclusions: "Efficiency tools" like copy/paste and templated text meant to reduce documentation burden and increase provider efficiency may have limited efficacy.